Motor evoked potentials in standing and recumbent calves induced by magnetic stimulation at the foramen magnum. (October 2016) - Rijckaert, J.; Pardon, B.; Verryken, K.; Van Ham, L.; van Loon, G.; Deprez, P.
Highlights: Magnetic stimulation is possible in calves at the level of the foramen magnum. Reference values were determined from 41 healthy Holstein Friesian bull calves. The effect of position (standing versus recumbency) was examined in 11 calves. Magnetic muscle evoked potentials are more difficult to obtain in calves in lateral recumbency than in standing calves. Abstract: The aims of this study were to determine reference values for magnetic motor evoked potentials (mMEPs) in calves and the influence of position during examination (standing or lateral recumbency). Reference values were determined using 41 healthy Holstein Friesian bull calves aged 1–10 months; standing and lateral recumbency were examined in 11 calves. Maximal magnetic stimulation was performed at the level of the foramen magnum with a magnetic field of 4 T at the coil surface. In standing position, distinct, reproducible mMEPs were obtained in all calves. Onset latency (LAT) (mean ± standard deviation) was significantly shorter in the thoracic limbs (34.4 ± 3.1 ms) than in the pelvic limbs (44.6 ± 3.0 ms). Amplitude (AMPL) was significantly higher in the thoracic limbs (3.7 ± 1.7 mV) than in the pelvic limbs (3.3 ± 1.7 mV) and significantly increased with body length. Age, body weight, height at the withers and rectal temperature had no significant association with LAT or AMPL, and no differences between left and right were noted. In the lateral position, only 64% of the calves showed responses in the four limbs; in these calves, LAT (29.7 ± 4.7 ms) and AMPL (3.0 ± 1.8 mV) in the thoracic limbs were significantly different from AMPL (47.0 ± 7.4 ms) and LAT (2.1 ± 2.1 mV) in the pelvic limbs. In conclusion, mMEPs in limb muscles can be evoked in calves by stimulation at the level of the foramen magnum. mMEPs are more difficult to obtain in lateral recumbency than in standing calves.